The Impact of Purinergic System Enzymes on Noncommunicable, Neurological, and Degenerative Diseases - Margarete Dulce Bagatini; Alessandra Antunes dos Santos; Andréia Machado Cardoso; Aline Mânica; Cristina Ruedell Reschke; Fabiano Barbosa Carvalho (Journal of Immunology Research)
Evidences show that purinergic signaling is involved in processes associated with health and disease, including noncommunicable, neurological, and degenerative diseases. These diseases strike from children to elderly and are generally characterized by progressive deterioration of cells, eventually leading to tissue or organ degeneration. These pathological conditions can be associated with disturbance in the signaling mediated by nucleotides and nucleosides of adenine, in expression or activity of extracellular ectonucleotidases and in activation of P2X and P2Y receptors. Among the best known of these diseases are atherosclerosis, hypertension, cancer, epilepsy, Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). The currently available treatments present limited effectiveness and are mostly palliative. This review aims to present the role of purinergic signaling highlighting the ectonucleotidases E-NTPDase, E-NPP, E-5′-nucleotidase, and adenosine deaminase in noncommunicable, neurological, and degenerative diseases associated with the cardiovascular and central nervous systems and cancer. In conclusion, changes in the activity of ectonucleotidases were verified in all reviewed diseases. Although the role of ectonucleotidases still remains to be further investigated, evidences reviewed here can contribute to a better understanding of the molecular mechanisms of highly complex diseases, which majorly impact on patients’ quality of life.